Alumino-oxy-rossmanite from pegmatites in Variscan metamorphic rocks from Eibenstein an der Thaya, Lower Austria, Austria: a new tourmaline that represents the most Al-rich end-member composition - Ertl, Andreas; Hughes, John M.; Prowatke, Stefan; Ludwig, Thomas; Lengauer, Christian L.; Meyer, Hans-Peter; Giester, Gerald; Kolitsch, Uwe; Prayer, Albert (American mineralogist, 2022)
Alumino-oxy-rossmanite, ideally ☐Al3Al6(Si5AlO18)(BO3)3(OH)3O, is here described as a new member of the tourmaline supergroup. It is an early magmatic Al-rich oxy-tourmaline from a small pegmatitic body embedded in amphibolite and biotite-rich paragneiss. This new pink tourmaline was found in a Moldanubian pegmatite (of the Drosendorf Unit) that occurs in a large quarry near the village of Eibenstein an der Thaya, Waidhofen an der Thaya district, Lower Austria, Austria. The empirical formula of the holotype was determined on the basis of electron microprobe analysis (EMPA), secondary ion mass spectrometry (SIMS), spectroscopical methods (optical absorption and infrared spectroscopy), and crystal-structure refinement (SREF) as X(☐0.53Na0.46Ca0.01) Y(Al2.37Mn0.213+Li0.16☐0.14Mn0.072+Fe0.033+Fe0.012+Ti0.014+) ZAl6(Si5.37Al0.41B0.22O18)(BO3)3V[(OH)2.77O0.23] W[O0.80(OH)0.15F0.05]. Chemical composition (wt%) is: SiO2 33.96, TiO2 0.10, Al2O3 47.08, B2O3 11.77, FeO 0.08, Fe2O3 0.23, MnO 0.52, Mn2O3 1.70, CaO 0.04, Li2O 0.25, ZnO 0.03, Na2O 1.51, H2O 2.79, F 0.09, total 100.11. The presence of relatively high amounts of trivalent Mn in alumino-oxy-rossmanite is in agreement with the observation that the OH groups are present at a lower concentration than commonly found in other Al-rich and Li-bearing tourmalines. The crystal structure of alumino-oxy-rossmanite [space group R3m; a = 15.803(1), c = 7.088(1) Å; V = 1532.9(3) Å3] was refined to an R1(F) value of 1.68%. The eight strongest X-ray diffraction lines in the (calculated) powder pattern [d in Å (I) hkl] are: 2.5534 (100) 051, 3.9508 (85) 220, 2.9236 (78) 122, 4.1783 (61) 211, 2.4307 (55) 012, 2.0198 (39) 152, 1.8995 (30) 342, 6.294 (28) 101. The most common associated minerals are quartz, albite, microcline, and apatite. Beryl and, in places, schorl are also found as primary pegmatitic phases. Because of the low mode of associated mica (muscovite), we assume that the silica melt, which formed this pegmatite, crystallized under relatively dry conditions, in agreement with the observation that alumino-oxy-rossmanite contains a lower amount of OH than most other tourmalines. This new member of the tourmaline supergroup exhibits the most Al-rich end-member composition of the tourmaline supergroup (theoretical content: ~54 wt% Al2O3). The significant content of tetrahedrally coordinated Al could reflect the relatively high-temperature conditions (~700 °C) inferred for crystallization of the pegmatite.Alumino-oxy-rossmanite was named for its chemical relationship to rossmanite, ☐(LiAl2)Al6(Si6O18) (BO3)3(OH)3(OH), which in turn was named after George R. Rossman, Professor of Mineralogy at the California Institute of Technology (Pasadena, California, U.S.A.).